2011
DOI: 10.1021/om200473c
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Hydrostannylation of Unactivated Alkenes with Chiral Trialkylstannanes

Abstract: Free radical hydrostannylation of olefins with differing steric and electronic demands have been carried out using the chiral, nonracemic stannanes (1R,2S,5R)-menthyldiphenyltin hydride (7), bis[(1R,2S,5R)-menthyl]phenyltin hydride (8), and tris[(1R,2S,5R)-menthyl]tin hydride (9). These reactions resulted in adducts 16–18 with yields that were found to depend on the nature of the substituents on both alkene and stannane and could be carried out at low temperature initiated by triethylborane and oxygen; MenPh2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[54][55][56] High concentrations of stannane or polarity-reversal catalysis 57 is often required to effect free radical hydrostannylation, especially with bulky stannanes. 58,59 When low concentrations of tin hydride are used, the alkenyl radical arising from the addition of the tin-centered radical onto the alkyne (or alkene) cannot be trapped fast enough to compete with b-fragmentation to regenerate the carbon-carbon multiple bond, effectively increasing the likelihood of stannyl radical attack at sulfur (Scheme 11). When problems are encountered, these can usually be overcome through the use of more hindered tin hydrides to prevent addition to the alkene or alkyne as illustrated in Scheme 11, eqn (a) and (b).…”
Section: Chemoselectivity Principlesmentioning
confidence: 99%
“…[54][55][56] High concentrations of stannane or polarity-reversal catalysis 57 is often required to effect free radical hydrostannylation, especially with bulky stannanes. 58,59 When low concentrations of tin hydride are used, the alkenyl radical arising from the addition of the tin-centered radical onto the alkyne (or alkene) cannot be trapped fast enough to compete with b-fragmentation to regenerate the carbon-carbon multiple bond, effectively increasing the likelihood of stannyl radical attack at sulfur (Scheme 11). When problems are encountered, these can usually be overcome through the use of more hindered tin hydrides to prevent addition to the alkene or alkyne as illustrated in Scheme 11, eqn (a) and (b).…”
Section: Chemoselectivity Principlesmentioning
confidence: 99%
“…Thus, a radical mechanism similar to that established for the photoinduced thiol-ene coupling (TEC) [7,8] can be outlined (Scheme 3). This C-P bond forming reaction, actually a phosphonylene coupling (PEC), owing to the mild and neutral conditions under which it occurs, enabled the introduction of the phosphonate group in sensitive biomolecules such as various alkenyl sugars.…”
Section: Discussionmentioning
confidence: 95%
“…One of these criteria involves atom economy, that is, the need for high conversion efficiency in terms of all atoms involved. [2,4] Other typical hydrofunctionalization reactions include hydroamination [5] (H-E = HNR 2 ), hydrosilylation [6] (H-E = HSiR 3 ), hydrostannylation [7] (H-E = HSnR 3 ), and hydrothiolation [5d,8] (H-E = HSR) of unactivated alkenes (Scheme 1). A prototypical example of this class of reactions is the hydroboration of alkenes (Scheme 1, H-E = HBR 2 ) discovered by H. C. Brown in the middle of the last century.…”
Section: Introductionmentioning
confidence: 99%
“…Single-enantiomer drug candidates are important to many pharmaceutical companies, and therefore, new methods for the preparation of enantiopure compounds are critical for the development of next-generation pharmaceutical products. 6 The use of microwave (MW) irradiation in organic synthesis has become a popular technique to develop and optimize the synthesis of libraries of compounds in short reaction time compare to those obtained with the classical thermal methods in pharmaceutical and academic production. 7 Numerous studies in the past ten years, demonstrated that microwave enhanced chemical reactions and that they are faster than conventional heating methods.…”
Section: Methodsmentioning
confidence: 99%